Monasticism Between Christianity and Islam - A Comparative Study - (Islamic Sciences Journal, 2023)
ABSTRACT                       Praise be to Allah, Lord of the Worlds, and prayers and peace be upon our Prophet Muhammad, may Allah’s prayers and peace be upon him, and upon all his family and companions, as for what follows.This is a summary of the research that I want to embark on, which is based on the study (monasticism between Christianity and Islam - a comparative study -)  The reason for choosing this study, in which I tried very hard to find an explanation of the concept of the word monasticism between Christianity and Islam, which is marred by ambiguity in many aspects. with an explanation of the words synonymous with the word monasticism, such as: (asceticism, seclusion, isolation) with an explanation of Islam's position on it, with mentioning the evidence for it from the Bible, as well as the evidence for its denial from the Qur'an and the Prophetic Sunnah.Accordingly, the scientific article has imposed on me that this research should consist of an introduction, a preface, and three chapters, followed by a conclusion, with a list of sources and references.Praise be to Allah, Lord of the Worlds, to His Truthful and Trustworthy Messenger, and to all his family and companions.